Economic cycle and economic consequences of the global SARS-CoV-2 pandemic in the Czech Republic - Volejníková, Jolana; Kuba, Ondřej (EDP Sciences - Web of Conferences, 2021)
Research background: The global SARS-CoV-2 pandemic is for human society unprecedented. Coronavirus is dramatically changing people's lives, and despite of uncertainty about the future, it is certain that its global consequences will have many dimensions. The significant economic impacts are unquestionable today. The Czech economy, like the rest of the world, is facing an unexpected exogenous shock. This manifests itself with varying intensity both at the level of sub-markets and on the side of aggregate supply and demand. It is literally a textbook example, explaining the outbreak of the downturn phase of the business cycle. Nevertheless, the sudden slowdown of economic activity as a result of the coronavirus pandemic, quarantine and the state of emergency, has many specificities across countries. Purpose of the article: The primary goal of this article is to analyze the economic consequences of the pandemic crisis in the reality of the Czech Republic. On this basis, it identifies the specifics of a pandemic crisis, in the context of a broader framework of economic theories of business cycles. Methods: The analytical part of the article is processed on the basis of publicly available statistical data and economic forecasts. The derivation and argumentation of the conclusions is based on an empiric-inductive approach, methods of synthesis and comparison. Findings & Value added: The article maps the direct and mediated economic contexts of the economic cycle caused by the coronavirus pandemic in the reality of the Czech Republic. It identifies the differences and specifics of the downward phase of the pandemic economic cycle and derives their possible long-term impacts. At the theoretical level, the ambition of the article is to bring new knowledge to the contemporary economic theory of business cycles.
Hospodářský cyklus a ekonomické konsekvence globální pandemie SARS-CoV-2 v České republice
Keywords: globalization; SARS-CoV-2; markets and the economy; business cycle theory; Czech Republic; globalizace; SARS-CoV-2; trhy a ekonomika; teorie hospodářských cyklů; Czech Republic